Prevalence of chronic musculoskeletal spinal injuries in the sport of artificial track luge - Morison, A.; Balliett, M.; Merkle, P.; Burke, J. (Science & Sports, 2016)
Purpose: The purpose of the study was to determine the frequency, location, type and severity of injuries to segmental regions of spine sustained by international luge athletes and conservative musculoskeletal approaches used to treat their injuries. Methods: Retrospective, self-reported injury and treatment data related to the purpose of this study were collected using a multi-language survey distributed to international luge athletes. Using Facebook contacts of luge athletes known to the principal investigator, Internet links to the survey (Qualtrics L.L.C., Provo, UT) were distributed to 150 athletes who were at least 18 years old and competed in the general class of luge (100 men, 50 women) via e-mail. Results: There were 64 respondents (42.7%). The annual rate of musculoskeletal injuries of the spine was 0.13 injuries per athlete per year. The most common musculoskeletal spinal injuries were sprains/strains (n = 24, 47.1%) and intervertebral disc injuries (n = 22, 43.1%). The majority of musculoskeletal spinal injuries were rated as mild to moderate in severity (69.1%) and persisted for more than 6 months (87.3%), making them chronic in nature. At least two-thirds of the injured athletes reported using massage, physical therapy, exercise or a form of complementary and alternative medicine (chiropractic or acupuncture) for their musculoskeletal spinal injuries. Of those athletes receiving chiropractic care for their musculoskeletal spinal injuries, perceived effectiveness of symptom relief for cervical and thoracic treatments was 100%, while perceived effectiveness of symptom relief for lumbar treatments was 86.7%. Conclusion: The majority of responding luge athletes (51.6%) experienced a musculoskeletal spinal injury during their career. Musculoskeletal spinal injuries were chronic in nature, mild to moderate in severity and predominately occurred in the lumbar and cervical spinal segments. Sprain/strain and intervertebral disc injures were the most commonly reported musculoskeletal spinal injuries. The role of chiropractic care as a cost-effective, conservative treatment modality for luge athletes requires further research and clinical consideration.